ASSESSMENT OF PSYCHOLOGICAL CHARACTERISTICS OF HUMAN RIGHTS IN THE SECURITY OF ITS WORK - Darya A. Melnikova; German N. Yagovkin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The effect of the psychological characteristics of the person to his personal safety. The role of motivation for Human Security. The classification of the causes of erroneous actions of man. The cases of deliberate violations of safety regulations. The influence of psychological factors on the adequate human behavior in emergency situations. A model that allows to comprehensively assess the impact of psychological factors on human security and its surrounding.